2006
DOI: 10.1007/bf02850345
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the relaxing effects of desflurane and sevoflurane on oxytocin-induced contractions of isolated myometrium in both pregnant and nonpregnant rats

Abstract: In this study, the effects of 2 volatile anesthetics, desflurane and sevoflurane, on oxytocin-induced contractions of isolated myometrium in pregnant and nonpregnant rats were compared. Twenty pregnant and 20 nonpregnant Wistar albino rats were studied at 19 to 20 days' gestation (term, 22 days). A total of 40 myometrial strips were obtained from pregnant and nonpregnant rats, and each of these was randomly assigned to 1 of 4 groups (n=10, each group). After spontaneous myometrial contractions were induced in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Other studies have found that sevoflurane reduces the force and frequency of oxytocin-induced myometrial contraction in myometrium isolated from humans [10] and rats [4,6]. Dogru et al reported that the highest measured levels of inhibition of the amplitude and frequency of myometrial contractions with sevoflurane (at 2 MAC) were 84% and 75%, respectively.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Other studies have found that sevoflurane reduces the force and frequency of oxytocin-induced myometrial contraction in myometrium isolated from humans [10] and rats [4,6]. Dogru et al reported that the highest measured levels of inhibition of the amplitude and frequency of myometrial contractions with sevoflurane (at 2 MAC) were 84% and 75%, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have reported that volatile anesthetics such as sevoflurane exert inhibitory effects on myometrial contraction in rats [4][5][6][7][8] and humans [9][10][11][12]. Similarly, propofol reportedly inhibits myometrial contraction in rats [13,14] and humans [15][16][17].…”
Section: Introductionmentioning
confidence: 96%
“…Bei je 20 trächtigen und nicht trächtigen Wistar-Ratten wurden Proben des Myometriums entnommen und die Wirkung von 0,5; 1o der 2M AC Sevofluran auf die spontane Kontraktionsfähigkeit untersucht. Es wurde bei allen, außer den gegen 0,5 MAC Sevofluran exponierten, nicht trächtigen Tieren eine Hemmung der Kontraktionsfähigkeit beobachtet (Gultekin et al 2006).…”
Section: Fertilitätunclassified